2020
DOI: 10.3390/plants9020235
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for In Vitro Shoot-Tip Culture and Sporophyte Production Using Selaginella martensii Spring Sporophyte

Abstract: Selaginella martensii, an evergreen perennial fern that is native to South America and New Zealand, is named “frosty fern” because of its beautiful white-colored leaves and it is used as an ornamental plant. Efficient propagation methods for this species have not been developed. We aimed to develop an efficient propagation method for S. martensii through in vitro culture. We investigated culture conditions that are suitable for shoot-tip proliferation and growth. The optimum shoot-tip culture conditions were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Similarly, the addition of 0.1% (w/v) AC improved the root number and length of Magnolia 'Ann' (Parris et al, 2012), and 1/4 MS medium with 1.0% (w/v) AC was the recorded optimum for the root development of fern plant Matteuccia struthiopteris (Thakur et al, 1998). In contrast, MS without AC was the most efficient for root development of plantlets in nonresurrection species Selaginella martensii (Park et al, 2020).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Similarly, the addition of 0.1% (w/v) AC improved the root number and length of Magnolia 'Ann' (Parris et al, 2012), and 1/4 MS medium with 1.0% (w/v) AC was the recorded optimum for the root development of fern plant Matteuccia struthiopteris (Thakur et al, 1998). In contrast, MS without AC was the most efficient for root development of plantlets in nonresurrection species Selaginella martensii (Park et al, 2020).…”
Section: Resultsmentioning
confidence: 90%
“…The same type of substrate was also suitable for the plantlet acclimatization of Cibotium barometz (Yu et al, 2017b). Nevertheless, a 3:1 mixture of horticultural substrate and decomposed granite favored the growth of acclimated plantlets in Selaginella martensii (Park et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jha [32] produced plants in medium containing plant-growth regulators for the propagation of Selaginella microphylla, whereas in the present study, we showed that S. tamariscina regeneration was possible in medium without plant-growth regulators. In addition, sporophyte explants from Selaginella martensii do not form new sporophytes; instead, they merely grow [21]. In contrast, S. tamariscina sporophyte explants regenerate several sporophytes and thus ensure effective propagation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro culture can produce homogeneous plants throughout the year in a controlled environment and promote their rapid propagation [20,21]. Additionally, this method can be used for species conservation and for propagating plants that are difficult to reproduce naturally [22].…”
Section: Introductionmentioning
confidence: 99%